The Technical Report: What is Continuum Zone Repetition on Popular Resistance Training Periodization - Kahraman, Yeli̇z (Universitas Negeri Semarang, 2023)
As resistance training periodization has recently been touted potential plan and program to regime, session and set-up. The continuum zone repetition has been associated with developing resistance training periodization to develop maximize performance, however it might be more far-reaching as either periodization relationship may be use continuum zone repetition strategy is poorly understood. To determine continuum zone repetition improved resistance training periodization through specAs resistance training periodization has recently been touted potential plan and program to regime, session and set-up. The continuum zone repetition has been associated with developing resistance training periodization to develop maximize performance, however it might be more far-reaching as either periodization relationship may be use continuum zone repetition strategy is poorly understood. To determine continuum zone repetition improved resistance training periodization through specific properties periodic repetition strategy. To date, continuum zone repetition on either current resistance training periodization or training regimes are common approach to produce equivocal maximize performance outcomes. Technical report research conducted on two electronic databases like Pubmed and Web of Science. Resolution for disparity due to continuum zone repetition seem to rarely researches. Exploration of the optimize performance relationship is required continuum zone repetition strategy to evaluate maximize strength, hypertrophy, endurance and power session. Until such studies are completed the efficiency of continuum zone repetition limited in popular resistance training periodizationific properties periodic repetition strategy. To date, continuum zone repetition on either current resistance training periodization or training regimes are common approach to produce equivocal maximize performance outcomes. Technical report research conducted on two electronic databases like Pubmed and Web of Science. Resolution for disparity due to continuum zone repetition seem to rarely researches. Exploration of the optimize performance relationship is required continuum zone repetition strategy to evaluate maximize strength, hypertrophy, endurance and power session. Until such studies are completed the efficiency of continuum zone repetition limited in popular resistance training periodization